Effects of low-dose aspirin on the prevention of preeclampsia and pregnancy outcomes: A randomized controlled trial from Shanghai, China. (May 2020) - Gu, Wei; Lin, Jing; Hou, Yan-Yan; Lin, Nan; Song, Meng-Fan; Zeng, Wei-Jian; Shang, Jing; Huang, He-Feng
Highlights: This RTC examined preeclampsia prevention using low-dose aspirin. Preventive and dose-dependent effects of aspirin on preeclampsia were confirmed. Aspirin's mechanism of action and effect on pregnancy outcomes are explained. We identified the most suitable population for preeclampsia prevention with aspirin. Abstract: Objectives: To evaluate the preventive effects of low-dose aspirin on the incidence of preeclampsia and pregnancy outcomes of women at high-risk for preeclampsia. Study design: This prospective randomized clinical trial was conducted at the Obstetrics Department of The International Peace Maternity and Child Health Hospital, School of Medicine, Shanghai Jiao Tong University, China. It analyzed data from 1105 high-risk women who were divided into the control group (placebo group) and the aspirin group (including three subgroups: 25 mg, 50 mg and 75 mg). The aspirin group in this study was instructed to take aspirin daily before bedtime beginning in the 12th week of pregnancy. Main outcome measures: The primary outcome is the occurrence of preeclampsia. The secondary outcomes included maternal and neonatal outcomes (such as premature delivery, FGR etc.), maternal serum biomarkers (including d -dimers, platelet aggregation rates, etc.) and uterine arterial blood flow resistance. The onset of preeclampsia and pregnancy outcomes were recorded after all participants delivered. Results: Low-dose aspirin significantly reduced the incidence of preeclampsia and early-onset preeclampsia. Aspirin also showed significant dose dependence in preeclampsia prevention. The results of Mantel-Haenszel trend test showed that there was a linear relationship between the dosage and the incidence of preeclampsia and early preeclampsia (P < 0.05). Pearson's results showed that the incidence of preeclampsia and early preeclampsia was negatively correlated with aspirin dosage. There was also a linear relationship between the dosage and the rates of postpartum hemorrhage, fetal growth restriction, premature births and cesarean section (P < 0.05). There was no evidence to suggest differences in the incidence of fetal distress, miscarriage and placental abruption among the four groups. The blood resistance S/D value of uterine artery in early pregnancy was the only independent factor affecting the efficacy of aspirin (OR = 1.405; 95 %CI, 1.058–1.867; P = 0.019). Conclusion: Low-dose aspirin can prevent preeclampsia and early-preeclampsia. Its efficacy is dose-dependent. It can reduce the rates of postpartum hemorrhage, fetal growth restriction, premature births and cesarean section. The prophylactic effect of aspirin on preeclampsia seemed to be greater in patients with higher blood resistance S/D value of uterine artery during early pregnancy.